How to Reduce Delayed Gastric Emptying After Pancreatoduodenectomy: A Systematic Literature Review and Meta-Analysis - Artur Rebelo, MD; Randi Kresse; Yoshiaki Sunami, PhD; Ulrich Ronellenfitsch, MD; Jörg Kleeff, MD; Johannes Klose, MD (Annals of Surgery Open)
Introduction:. The occurrence of delayed gastric emptying (DGE) following pancreatoduodenectomy is of high clinical relevance. Despite the pivotal nature of this topic, the existing evidence is limited and often conflicting. This meta-analysis aims to assess the impact of various interventions, such as the type of surgical reconstruction (specifically pylorus resection or preservation), enhanced recovery after surgery (ERAS), epidural anesthesia (EA), as well as strategies involving nasogastric decompression on DGE. Methods:. Following the PRISMA guidelines, a systematic search was conducted. Studies that compared patients undergoing pancreatoduodenectomy regarding one of the following interventions were included: pylorus-preserving pancreaticoduodenectomy (ppPD) versus pylorus-resecting pancreaticoduodenectomy (prPD), ERAS versus no ERAS, epidural anesthesia EA versus no EA, nasogastric decompression versus no nasogastric decompression and jejunostomy/nasojejunal feeding tube placement (J/NJF) versus no J/NJF. Results:. The analysis included 5930 patients from 29 studies. Patients undergoing ppPD exhibited a higher incidence of DGE compared with those undergoing prPD (logOR, −0.95; 95% CI = −1.57 to −0.34; P = 0.002). Additionally, patients in the ERAS group showed reduced rates of DGE (logOR, −0.712; 95% CI = −1.242 to −0.183; P = 0.008). Lower rates of DGE were observed in patients without a J/NJF (logOR, −0.618; 95% CI, 0.39–0.84; P < 0.001). Conclusion:. In summary, our meta-analysis reveals that pylorus resection, adherence to ERAS protocols, and the absence of a J/NJF are associated with lower rates of DGE after pancreatoduodenectomy. Although these results are partially based on observational studies, they contribute valuable insights to the current understanding of interventions impacting DGE in these complex procedures.